2006
DOI: 10.1051/vetres:2005048
|View full text |Cite
|
Sign up to set email alerts
|

Maedi-visna virus infection of ovine mammary epithelial cells

Abstract: -The aim of this work was to perform a complete study of maedi-visna virus (MVV) infected mammary glands of naturally-infected sheep, and to determine if cells other than macrophages undergo a productive viral infection in this organ. Fifteen seropositive and two seronegative ewes were selected from MVV-infected flocks on the basis of clinical indurative mastitis and three sheep from an MVV-free flock. Within the mammary gland, MVV-positive cells were located by immunohistochemistry in the stroma and the epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
0
15
1
7
Order By: Relevance
“…The presence of OPPV CA in alveolar macrophages of the mammary gland is consistent with previous research where viral RNA and CA have been found in sheep mammary cells with the morphology of macrophages. 6,8,23,39 These combined results suggest that CD163-or CD172a-positive alveolar macrophages acquired OPPV CA by phagocytosis of CA, whole virus, or virusinfected cells and/or by receptor-mediated endocytosis of whole virus. HIV can infect cells using receptor-mediated endocytosis via dynamin; thus, OPPV could have a similar way of infecting alveolar macrophages.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of OPPV CA in alveolar macrophages of the mammary gland is consistent with previous research where viral RNA and CA have been found in sheep mammary cells with the morphology of macrophages. 6,8,23,39 These combined results suggest that CD163-or CD172a-positive alveolar macrophages acquired OPPV CA by phagocytosis of CA, whole virus, or virusinfected cells and/or by receptor-mediated endocytosis of whole virus. HIV can infect cells using receptor-mediated endocytosis via dynamin; thus, OPPV could have a similar way of infecting alveolar macrophages.…”
Section: Discussionmentioning
confidence: 87%
“…Other cell types permissive for small ruminant lentivirus infection are microglia 18 ; dendritic cells 2 ; epithelial cells from the lung 19 ; mammary gland 20 ; third eye lid 21 ; kidney 22 ; uterus and epididymis23, 24 and endothelium; smooth myocytes19, 25; granulosa cells 26 ; and parenchyma cells from the liver and heart 27 …”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, lymphoid follicles with or without germinal centres develop. Virus can be detected using in situ hybridization and PCR techniques in macrophages and in ductal epithelial cells, and isolated from epithelial cells from explanted mammary tissue [14,264]. The lesions are thus thought to be progressive.…”
Section: Mastitismentioning
confidence: 99%